2020
DOI: 10.2196/22767
|View full text |Cite
|
Sign up to set email alerts
|

Intergroup Contact, COVID-19 News Consumption, and the Moderating Role of Digital Media Trust on Prejudice Toward Asians in the United States: Cross-Sectional Study

Abstract: Background The perceived threat of a contagious virus may lead people to be distrustful of immigrants and out-groups. Since the COVID-19 outbreak, the salient politicized discourses of blaming Chinese people for spreading the virus have fueled over 2000 reports of anti-Asian racial incidents and hate crimes in the United States. Objective The study aims to investigate the relationships between news consumption, trust, intergroup contact, and prejudicial… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(46 citation statements)
references
References 51 publications
2
43
0
1
Order By: Relevance
“…The penetration of social media has undoubtedly increased over recent years, that is what probably makes COVID-19 different and socially more alarming than many other fatal epidemics that occurred earlier like the Spanish flu and cholera, where communication was highly restricted to certain pockets in the absence of such widespread penetration of social media ( 23 ). Croucher et al ( 31 ) reported increased xenophobic sentiments, social stigma, racism and prejudice against the “Asian” communities in the United States (U.S.) due to increased use of social media during the pandemic. The results revealed that participants tend to believe the “facts” shared on social media as “truths,” gender differences in the type of prejudice (intergroup anxiety for men and a symbolic threat for women), and enhanced chances of viewing the “Chinese” as a threat in those with increased usage of social media.…”
Section: Covid-19 As An “Infodemic” In Public Health: the Impactmentioning
confidence: 99%
“…The penetration of social media has undoubtedly increased over recent years, that is what probably makes COVID-19 different and socially more alarming than many other fatal epidemics that occurred earlier like the Spanish flu and cholera, where communication was highly restricted to certain pockets in the absence of such widespread penetration of social media ( 23 ). Croucher et al ( 31 ) reported increased xenophobic sentiments, social stigma, racism and prejudice against the “Asian” communities in the United States (U.S.) due to increased use of social media during the pandemic. The results revealed that participants tend to believe the “facts” shared on social media as “truths,” gender differences in the type of prejudice (intergroup anxiety for men and a symbolic threat for women), and enhanced chances of viewing the “Chinese” as a threat in those with increased usage of social media.…”
Section: Covid-19 As An “Infodemic” In Public Health: the Impactmentioning
confidence: 99%
“…East and Southeast Asian communities and individuals have been targeted globally with hate speech, including slurs, dehumanization, and slanderous, stereotyping comments about Chinese cuisine (Albader, 2020 ; Hu et al, 2020 ; Tahmasbi et al, 2021 ). Anti-Asian hate-crimes reports also spiked since the beginning of the pandemic in North America (Edara, 2020 ; Gover et al, 2020 ; Kotyk, 2020 ; Tessler et al, 2020 ; Tsai et al, 2020 ), Europe (Gao and Sai, 2020 ; Pellegrino, 2020 ; Velásquez et al, 2020 , preprint) and Australia (Furlong and Finnie, 2020 ). In India, people from northeastern states with more phenotypically East Asian features have been discriminated against and attacked (Haokip, 2020 ).…”
Section: Within-society Intergroup Relationsmentioning
confidence: 99%
“…Unfortunately, the increase in hate crimes and discrimination against individuals of Asian descent in some regions should also be taken into consideration by physicians considering studying in Western countries. 13) In Japan, research activities were temporarily suspended after the first State Emergency Declaration. This has been an obstacle for graduate students who are on timely restrictions to produce research results.…”
Section: Issues Encountered By Physicians During the Covid-19 Pandemicmentioning
confidence: 99%